Experimental study on the influence of maintenance track position on vortex-induced vibration performance of a box girder suspension bridge - Li, Chunguang; Yan, Hubin; Zou, Minhao; Han, Yan; Cai, C. S.; Wang, Long (Frontiers in Built Environment, 2023)
To study the influence of maintenance track on the vortex-induced vibration (VIV) performance of main girder, the VIV response and time history of surface pressure data of a section model were obtained by wind tunnel vibration and pressure measurements for a large-span steel box girder suspension bridge. The VIV performance of the main girder was tested at ± 5° attack angles of various maintenance track positions, including 1, 2.5 and 5 m away from the outer edge of the girder bottom plate. The mean values, root variances and amplitude spectra of vortex-induced force and the correlation and contribution coefficients of local aerodynamic force to overall aerodynamic force were analyzed. The results show that when the maintenance track is 1 m away from the outer edge of the bottom plate, the main girder exhibits the worst VIV performance with a maximum amplitude of 0.457 m, far beyond the allowable value of the specification. The VIV performance of the main girder was greatly improved by moving the maintenance track inward. The pressure analysis indicates that the large pressure fluctuation at the front and rear parts of the upper surface is attributed to the strong VIV of the main girder. In this sense, the improved VIV performance is mainly contributed by the weakening of pressure fluctuation in these two areas and the reduced local aerodynamic force. When the distance between the maintenance track and bottom plate is adjusted to 2.5 m, a 3.5 m wind barrier with a ventilation rate of 30% effectively inhibits the VIV of the box girder. The main reason for the suppression is that the elimination of pressure fluctuation on the upper surface of the girder disturbs the correlation between local aerodynamic force and overall aerodynamic force, consequently diminishing the contribution of local aerodynamic force to the vortex-induced force.